Natural compounds protect against the pathogenesis of osteoarthritis by mediating the NRF2/ARE signaling - Wu, Zhenyu; Yang, Zhouxin; Liu, Luying; Xiao, Yong (Frontiers in Pharmacology, 2023)
Osteoarthritis (OA), a chronic joint cartilage disease, is characterized by the imbalanced homeostasis between anabolism and catabolism. Oxidative stress contributes to inflammatory responses, extracellular matrix (ECM) degradation, and chondrocyte apoptosis and promotes the pathogenesis of OA. Nuclear factor erythroid 2-related factor 2 (NRF2) is a central regulator of intracellular redox homeostasis. Activation of the NRF2/ARE signaling may effectively suppress oxidative stress, attenuate ECM degradation, and inhibit chondrocyte apoptosis. Increasing evidence suggests that the NRF2/ARE signaling has become a potential target for the therapeutic management of OA. Natural compounds, such as polyphenols and terpenoids, have been explored to protect against OA cartilage degeneration by activating the NRF2/ARE pathway. Specifically, flavonoids may function as NRF2 activators and exhibit chondroprotective activity. In conclusion, natural compounds provide rich resources to explore the therapeutic management of OA by activating NRF2/ARE signaling.